The effect of father-absence on the personality of male Jamaican adolescents - Wong, Joy Edris (1984)
This study sought to investigate the effect of father absence and female dominance in the home and school on certain personality characteristics and other variables related to the behaviour of adolescent boys in Jamaica, namely, aggression, self-concept, responsibility, opinion of male/female relationships, opinion of women, socio-economic status, and school type. Questionnaires were administered to a sample of 228 boys, randomly selected from Grade 11 of four co-educational secondary high and four New Secondary schools in Kingston and St. Andrew. Analysis of the data revealed: 1) no significant difference between father absent and father present boys on the personality variables. Female dominance in the home and in the school combined differentiated significantly between father-absent and father-present boys. High female dominance in the home and school was associated with father absence; 2) there was no significant difference in the personality variable between boys who had an older male presence (apart from the father) in the home and those who did not; 3) boys experiencing high female dominance in the home had a significantly more unfavourable opinion of women than those receiving low female dominance; 4) high female dominance in the school was associated with low responsibility, low opinion of male/female relationships, and low opinion of women, with responsibility emerging as the most significant discriminator; 5) high female dominance in the home was strongly related to high female dominance in the school, and significantly related to low opinion of male/female relationships and of women; 6) boys who scored high on responsibility tended to have low scores on aggression, high self-concepts, a healthy opinion of male/female relationships, and a high opinion of women; and 7) boys who felt that they were highly female dominated tended to have low self-concepts
Keywords: Home environment